Electricity balancing as a market equilibrium - Anselm Eicke; Oliver Ruhnau; Lion Hirth (ZBW - Leibniz Information Centre for Economics, 2021)
Frequency stability requires equalizing supply and demand for electricity at short time scales. Such electricity balancing is often understood as a sequential process in which random shocks, such as weather events, cause imbalances that system operators close by activating balancing reserves. By contrast, we study electricity balancing as a market where the equilibrium price (imbalance price) and quantity (system imbalance) are determined by supply and demand. System operators supply imbalance energy by activating reserves; market parties that, deliberately or not, deviate from schedules create a demand for imbalance energy. The incentives for deliberate strategic deviations emerge from wholesale market prices and the imbalance price. We empirically estimate the demand curve of imbalance energy, which describes how sensitive market parties are to imbalance prices. To overcome the classical endogeneity problem of price and quantity, we deploy instruments derived from a novel theoretical framework. Using data from Germany, we find a decline in the system imbalance by 2.2 MW for each increase in the imbalance price by EUR 1 per MWh. This significant price response is remarkable because the German regulator prohibits strategic deviations. We also estimate cross-market equilibriums between intraday and imbalance markets, finding that a shock to the imbalance price triggers a subsequent adjustment of the intraday price.
Additional information: Please cite as: Eicke, Anselm, Oliver Ruhnau & Lion Hirth (2021): “Electricity balancing as a market equilibrium: An instrument-based estimation of supply and demand for imbalance energy”, Energy Economics, https://doi.org/10.1016/j.eneco.2021.105455; More recent version: https://doi.org/10.1016/j.eneco.2021.105455
Keywords: Q41; L51; 330; Electricity Balancing; Intraday electricity market; Imbalance energy